Multi-Criteria Decision Making on the position of High Water Mark - Liu, Xin; Xia, Jianhong (Cecilia); Wright, Graeme; Arnold, Lesley; Liu, Q. (Elsevier, 2014)
As a cadastral boundary to separate water and land, the HighWater Mark (HWM) is important for coastal management and planning. However, contemporary research has failed to reach consensus on methods for HWM determination because of continual changes in tidal levels, together with unimpeded wave runup and the erosion and accretion of shorelines, which make it difficult to determine an agreeable position of the HWM. In this paper, a consistent and robust methodology is presented for the determination of the HWM over space and time. Existing HWM indicators are evaluated based on three criteria: precision, stability and inundation risk. These indicators are then integrated into a Multi-Criteria Decision Making (MCDM) model to assist in selecting the most suitable HWM determination methods for different purposes, such as coastal management or planning. The methodology is implemented using two coastal case studies inWestern Australia for testing the robustness of the developed methodology intwo distinctly different coastal environments. Research results show that the position of the dune toe is the most suitable indicator of the HWM for coastal hazards planning, and spatial continuity of tidal probability (SCTP) is the most ideal HWM for coastal property management purposes.